Peran Konseling Lintas Budaya Dalam Menghadapi Fenomena Gegar Budaya Serta Sebagai Upaya Meningkatkan Karakter Toleransi Pada Siswa Perantau - Cahyani, Anugrah Intan (Universitas Muria Kudus, 2018)
The issue of conflict between ethnic groups and cultures is not a new thing among Indonesians. The conflict that is closely related to the world of education is brawl between students. Such mistakes and misunderstandings lead to cultural shocks experienced by a particular person or group. For immigrants from tribes and other areas newly entering new environments are particularly vulnerable to cultural shocks. Cultural shock or culture shock can also be one of the triggers of a conflict in an environment where it has a different culture. The counselor as one of the educators is expected to be able to help and contribute in facing the cultural issues that often arise, especially in the education world. One of the efforts that can be done is to instill tolerance through cross-cultural counseling services. Character education through cross-cultural counseling services is expected to generate tolerance for the differences, as well as to help individuals who experience culture shock or culture shock in a new environment.